Forced Convection Heat Transfer in V-Pattern Folded Core Sandwich Structures - Sifeng Li; Zhijin Wang; Chen Zhou (International Journal of Aerospace Engineering)
Fully developed laminar flow and heat transfer performance of V-pattern folded core sandwich structures subjected to forced convection are numerically investigated. Based on the periodic feature of folded core, a methodology to simulate the fully developed flow and heat transfer state with a few unit cells is developed. The influences of geometric parameters on the coolant flow resistance and heat transfer behaviour are evaluated. Afterwards, approximate models are established based on design to optimize the heat dissipation efficiency. Design variables considered are geometric parameters of the V-pattern folded core, while the corresponding relative density is taken as a constraint. The simulation results show that the presented methodology makes it possible to analyse the fully developed regime with less computing resources. It is found that both pressure drop and heat transfer rate increase with the tortuosity of the flow channel and the inclination of the folded core. The optimization generates a design with a mildly tortuous feature in the streamwise direction to gain a maximum of heat dissipation efficiency under the current conditions.